2013
DOI: 10.4082/kjfm.2013.34.5.347
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Pain and Depression, Anxiety, and Cognitive Function among Advanced Cancer Patients in the Hospice Ward

Abstract: BackgroundPain is the most common but severe physical symptom among cancer patients. This study aimed to identify correlation between pain and psychological symptoms for terminal cancer patients.MethodsThe total sample consisted of 69 subjects who were recruited through two hospice wards, limited to patients who were mentally alert and had no psychiatric diseases. The subjects were divided into two groups according to the numerical rating scale: the pain-free group, 0 to 3 points; and the pain group, 4 to 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…This is not unexpected as depressive and anxiety disorders have been shown to be associated with worse pain severity over time [30], and pain has been shown to significantly correlate with depression in patients with advanced cancer [31]. We would hypothesize that at least some of the Anxiety/Depression benefits observed are linked to effective control of disease.…”
Section: Discussionmentioning
confidence: 93%
“…This is not unexpected as depressive and anxiety disorders have been shown to be associated with worse pain severity over time [30], and pain has been shown to significantly correlate with depression in patients with advanced cancer [31]. We would hypothesize that at least some of the Anxiety/Depression benefits observed are linked to effective control of disease.…”
Section: Discussionmentioning
confidence: 93%
“…The subscale scores of the PCQ were not significantly different between the groups. However, a helplessness subscale score of 19 (17)(18)(19)(20)(21)(22) and a selfcoping subscale score of 23,50 (12,25) were the highest scores. The group comparisons for the HADS and the OAU are shown in Table 4.…”
Section: Resultsmentioning
confidence: 98%
“…[2,[23][24][25][26][27] It has been suggested that anxiety and depression independently contributed to the emergence of mental health and somatic symptoms, [27] pain-aggravated mood disorders. [25] Thus, a significant correlation between physical symptoms, such as pain, and depression and/or anxiety might be more common in depressed cancer patients. [26] However, in some studies, depression was found to be more prominent than anxiety; therefore, pain has been suggested to directly correlate with depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, 69 patients (29.3%) had a PHQ‐9 score of ≥10, which is slightly higher than that found in a previous study that used the same criteria and was probably caused by our inclusion of patients with metastatic and advanced disease. Ko et al reported that about 60% of cancer patients had depression in a hospice ward in Korea . However, comparisons are problematic because the prevalence of depression among cancer patients could be affected by physical condition, disease progression, metastasis, and other factors, and thus, prevalence rates should be compared in similar backgrounds …”
Section: Discussionmentioning
confidence: 99%